Emma Khanzadyan - Bobokhyan, Arsen (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
Emma Khanzadyan (1922-2007) can be ranked among the greatest representatives of Armenian archaeology of the 20th century. Her life-path and career essentially characterise a special human being and a devoted scientist of distinguished ability. E. Khanzadyan was born into a family of musicians. She demonstrated her musical abilities in her school years, and in 1942-1943 even worked as a cello teacher. However, it happened that she became a student of the faculty of history at Yerevan State University (1943-1950). On graduating, Emma acquired a position at the Museum of Armenian History (1952-1959), at the same time continuing her post-graduate studies (1958-1960). Music was never forgotten, and she continued, of course, her musical education as well. In this context, it is not at all surprising in the least that Emma’s first article (1959) was dedicated to the musical instruments of ancient Armenia; this was a subconscious attempt to synthesise art with scholarship. Only years later, when she had an opportunity for independent excavations, did she finally acknowledge herself as an ‘archaeologist’.